Pengaruh Efektivitas dan Efisiensi Pelaporan KPI (Key Performance Indicator) Mingguan Terhadap Produktivitas Kerja pada Masa Transisi Digital di PT Wahana Internet Nusantara - Nimas Ayu Astuti; Aprilia Puspasari (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Digital transformation in performance reporting systems encourages organizations to enhance the effectiveness and efficiency of employee performance. One such effort is the transition from manual reporting to a digital system based on HRIS (Human Resource Information System). This study aims to determine the influence of the effectiveness and efficiency of weekly Key Performance Indicator (KPI) reporting on employee work productivity during the digital system transition at PT Wahana Internet Nusantara.This research used a quantitative method with a saturated sampling technique involving 47 respondents. Data were collected through questionnaires, and multiple linear regression analysis was performed using SPSS version 27. The results showed that partially, the effectiveness of KPI reporting did not significantly affect work productivity, whereas efficiency had a positive and significant influence. Simultaneously, both variables significantly affected work productivity. The coefficient of determination (R²) value of 0.422 indicates that the effectiveness and efficiency of KPI reporting contribute 42.2% to work productivity, while the remaining 57.8% is influenced by other variables not examined in this study.